Corneal elevation topographic maps assessing different diseases detection: A review - Ahmed S.M.; See O.H.; Weng L.Y.; Al-Sharify N.T.; Nser H.Y.; Al-Sharify Z.T.; Ghaeb N.H. (Ain Shams University, 2025)
The cornea is the human eye's transparent outermost layer. It plays a significant role in keeping the eyeball's shape and preventing infections with protective functions for the different structures within the eye. Cornea, like other tissue in the body, is affected by different diseases such as keratoconus. Detection of this disease is important for that reason variety of techniques and tools such as anterior and posterior topographical images of the human cornea are used. They are becoming more critical in categorizing healthy/unhealthy corneas. The outcomes of topographic device contain four different maps as well as other valuable parameters. Elevation maps are representing the elevation of corneal surfaces above and below reference surface. They were used along with elevation values by the researchers for both interior/posterior surfaces. These maps are affected by any change in other topographic parameters such as asphericity and toricity. These parameters were found to be essential to distinguish between normal and diseased eyes with the help of different feature selections or feature extraction, which is used to determine the most influential parameters that will contribute to the final decision. Some researchers highlighted the importance of the skewing angle of the bowtie shape, which indicates the cornea's health. This paper aims to explain the importance of elevation maps, artificial intelligent techniques and different parameters collected from different methods to identify if the cornea is diseased or healthy. ? 2023 THE AUTHORS